2010
DOI: 10.1016/j.bbrc.2010.09.125
|View full text |Cite
|
Sign up to set email alerts
|

The tick saliva immunosuppressor, Salp15, contributes to Th17-induced pathology during Experimental Autoimmune Encephalomyelitis

Abstract: Summary Salp15 is a tick saliva protein that inhibits CD4+ T cell differentiation through its interaction with CD4. The protein inhibits early signaling events during T cell activation and IL-2 production. Because murine experimental autoimmune encephalomyelitis development is mediated by central nervous system-infiltrating CD4+ T cells that are specific for myelin-associated proteins, we sought to determine whether the treatment of mice with Salp15 during EAE induction would prevent the generation of proinfla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 30 publications
1
13
0
2
Order By: Relevance
“…Similar results, showing that tick saliva inhibits the Th17 subset, were reported by Skallova and colleagues, who showed that saliva-exposed DCs failed to induce efficient Th1 and Th17 polarization and promoted development of Th2 responses (42). Interestingly, treatment with Salp15, which also inhibits IL-6 production in dendritic cells, was shown to increase the differentiation of Th17 cells in vivo, as evidenced by higher IL-17 production from PLP139-151-specific CD4 ϩ T cells isolated from the central nervous system and the periphery (43).…”
Section: Discussionmentioning
confidence: 75%
“…Similar results, showing that tick saliva inhibits the Th17 subset, were reported by Skallova and colleagues, who showed that saliva-exposed DCs failed to induce efficient Th1 and Th17 polarization and promoted development of Th2 responses (42). Interestingly, treatment with Salp15, which also inhibits IL-6 production in dendritic cells, was shown to increase the differentiation of Th17 cells in vivo, as evidenced by higher IL-17 production from PLP139-151-specific CD4 ϩ T cells isolated from the central nervous system and the periphery (43).…”
Section: Discussionmentioning
confidence: 75%
“…Furthermore, flow cytometry was used to detect the binding of Salp15 to CD4 for up to 72 h; the results suggested that the binding reaction between CD4 and salivary protein is persistent (65). However, deletion of the salivary protein C-terminal peptide P11 (Salp15 P11) results in a significant reduction in the capacity of Salp15 to bind to CD4+ T cells and a consequential lack of biological activity (65,66). Understanding the function and conformation of Salp15 can facilitate the development of highly specific pharmacological agents, such as monoclonal antibodies (mAbs) or Salp 15-like peptides, for special uses.…”
Section: Salp15 Exhibits Specific Interaction With Cd4mentioning
confidence: 99%
“…The Th17 can promote neutrophilic inflammation in the development of AHR; such inflammation is related to the severity of asthma (100,101). However, Juncadella et al (66) showed that the differentiation of Th17 cells is increased in the presence of Salp15, both in vivo and in vitro.…”
Section: Salp15 As a Potential Therapeutic Candidate For Allergic Asthmamentioning
confidence: 99%
See 2 more Smart Citations